1991
DOI: 10.1093/infdis/163.4.858
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and Genomic Diversity within Group A Respiratory Syncytial Virus

Abstract: Antigenic analysis using monoclonal antibodies and genomic analysis using ribonuclease protection was done on 47 isolates of group A respiratory syncytial virus (RSV) recovered from children in St. Louis during four RSV seasons. Antigenic analysis identified four subgroups; of the three that included more than one member, those designated A/2 and A/2V had characteristic ribonuclease protection patterns. A third subgroup, A/4, exhibited more extensive genomic heterogeneity, but all isolates were distinguishable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 12 publications
5
33
0
Order By: Relevance
“…20 The technique has been used to obtain new information about intrasubgroup variation and to characterize a collection of subgroup A human RSV isolates recovered from children with RSV infection in 1 metropolitan area during 4 different RSV seasons. 28 Four intrasubgroups were identified. An epidemiologic analysis of isolates in 1 of these intrasubgroups revealed that the protection fragments of isolates within each epidemic season were indistinguishable from one another but differed from those recovered during different epidemic seasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The technique has been used to obtain new information about intrasubgroup variation and to characterize a collection of subgroup A human RSV isolates recovered from children with RSV infection in 1 metropolitan area during 4 different RSV seasons. 28 Four intrasubgroups were identified. An epidemiologic analysis of isolates in 1 of these intrasubgroups revealed that the protection fragments of isolates within each epidemic season were indistinguishable from one another but differed from those recovered during different epidemic seasons.…”
Section: Discussionmentioning
confidence: 99%
“…This specificity may explain the occurrence of repeated infections with RSV and would have important implications for vaccine development. 28 Studies have not yet been done with RPA to determine whether corresponding genetic variations exist in viral proteins other than the G glycoprotein among the ruminant RSV isolates. Studies on the nucleotide sequence of the small hydrophobic (SH) protein have identified a significant degree of divergence between the SH protein of ovine RSV and that of bovine RSV.…”
Section: Discussionmentioning
confidence: 99%
“…These results also suggest that isolates may need to be characterized as to both group and genotype to fully understand protective immunity after natural infection and efficacy studies of candidate vaccines. nucleoprotein (N), phosphoprotein (P), small hydrophobic (SH) protein and attachment (G) protein genes have confirmed the division of HRSV into two groups and also identified numerous variants or lineages within each group (Johnson et al, 1987 b ;, 1995Cristina et al, 1991 ;Storch et al, 1991 ;Sullender et al, 1991 ;Cane et al, , 1994Garcia et al, 1994 ;Sanz et al, 1994).…”
Section: Introductionmentioning
confidence: 92%
“…On the basis of monoclonal antibody studies, HRSV has been classified into two major groups, A and B (Mufson et al, 1985 ;Anderson et al, 1985), and within these groups, antigenic variants or types of HRSV have also been identified (Hendry et al, 1986 ;A H kerlind et al, 1988 ;Mufson et al, 1988 ;Anderson et al, 1991 ;Storch et al, 1991). Sequence studies of the occurred each year such that no genotype or subtype predominated for more than 1 of the 5 study years.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were previously detected in human respiratory viruses too, when it seemed that viruses of a given antigenic group are homogenous. Increased amounts of data on different strains of the virus made us believe that antigenic and structural differences exist within individual groups (Morgan et al, 1987;Orvell et al, 1987;Storch et al, 1991). The above-mentioned impossibility to classify some BRSV viruses into antigenic groups and two reactivity pa�erns of B group viruses with G-specific monoclonal antibodies suggest that similar antigenic differences also exist in BRS viruses.…”
Section: Antigenic Variabilitymentioning
confidence: 99%